PPARγ inhibitors enhance the efficacy of statin therapy for steroid-induced osteonecrosis of the femoral head by directly inhibiting apoptosis and indirectly modulating lipoprotein subfractions - Kai-Yun Chen; Xu-huan Li; Dan Chen; Shi-da Qian; Run-hong Mei; Qian Li; Xue-feng Yu; Xi-jing He (PLoS ONE, 2025)
Background Steroid-induced osteonecrosis of the femoral head (SONFH) is a serious bone disease commonly seen in patients on long-term glucocorticoid therapy. Although statins have shown some efficacy in improving lipid metabolism, their efficacy in the treatment of SONFH remains limited. PPARγ inhibitors may enhance the efficacy of statins through several mechanisms. This study aims to investigate how PPARγ inhibitors may enhance the effects of statins in the treatment of SONFH by directly inhibiting apoptosis and indirectly modulating lipoprotein subfractions. Methods We first treated osteoblasts in vitro with high concentrations of hormones to simulate the SONFH environment. We then treated the cells with either the PPARγ inhibitor GW9662, the statin lovastatin, or a combination of both. We assessed cell proliferation and apoptosis using CCK-8, flow cytometry and Western blotting. We then established a SONFH rabbit model using high doses of methylprednisolone and lipopolysaccharide. The rabbits were randomly divided into four groups: control group, lovastatin group, GW9662 group and combination therapy group. We observed hip joint MRI before treatment, after 4 weeks of treatment, and 4 weeks after stopping treatment. We performed hematoxylin-eosin staining of the femoral head and analysed serum lipoprotein subfractions using VAP technology. In addition, we used quantitative polymerase chain reaction (qPCR) to analyse the expression of genes related to lipid metabolism at week 3. Results In vitro experiments showed that both GW9662 and lovastatin effectively inhibited hormone-induced apoptosis. In the animal studies, imaging and pathological results showed that the progression of SONFH was slower in the combination therapy group than in the other groups. VAP analysis showed that the lovastatin group had disturbed lipoprotein subfractions at the fourth week after stopping treatment, while the combination therapy group had more stable lipoprotein subfractions. Conclusion PPARγ inhibitors significantly enhance the efficacy of statins in the treatment of SONFH by directly inhibiting apoptosis and indirectly modulating lipoprotein subfractions. These findings provide new insights into the clinical management of SONFH and suggest that combination therapy may be an effective strategy.